Pendapatan Petani Garam Di Kecamatan Randangan Kabupaten Pohuwato Provinsi Gorontalo Kawasan Teluk Tomini - Tuli, Munirah; Tanpu, Funco; Tampoy, Wahhyuda Mahendra (Universitas Mataram, 2025)
One of the potentials of the marine and fisheries sector that can be explored is salt. Salt is a basic need and daily consumption of the Indonesian people. The purpose of this study was to determine the Level of Income of Salt Farmers and Salt Marketing Margins in Siduwonge Village, Randangan District, Pohuwato Regency. This study is useful for providing information or knowledge that can be used as a reference for the Level of Income of Salt Farmers and Salt Marketing Margins. The study was conducted on July 20, 2020 - August 20, 2020 in Pohuwato Regency, Gorontalo Province. The location of the data collection activity was carried out in Siduwongi Village, Randangan District, Pohuwato Regency. The method used in collecting data in field work practices is the survey method. Based on the results of the study in Siduwonge Village, Randangan District, Pohuwato Regency, it can be concluded that the level of net income of salt farmers in each group, namely, Karya Baru Rp. 4,348,000, Surya Motilango Rp. 3,529,000, Bintang Poliyama Rp. 3,172,000, Pelangi Rp. 2,420,000, Anggrek Rp. 2,162,600, Bintang Segiri Rp. 2,118,500, and Beringin Rp. 1,867,000. The average feasibility of the salt farmer business in Siduwomge Village is very feasible because the R/C in each group is more than 1